2008
DOI: 10.1017/s0029665108008690
|View full text |Cite
|
Sign up to set email alerts
|

Session 3: Joint Nutrition Society and Irish Nutrition and Dietetic Institute Symposium on ‘Nutrition and autoimmune disease’ PUFA, inflammatory processes and rheumatoid arthritis

Abstract: Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease manifested by swollen and painful joints, bone erosion and functional impairment. The joint lesions are characterised by infiltration of T lymphocytes, macrophages and B lymphocytes into the synovium and by synovial inflammation involving eicosanoids, cytokines and matrix metalloproteinases. In relation to inflammatory processes, the main fatty acids of interest are the n-6 PUFA arachidonic acid, which is the precursor of inflammatory eicos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 99 publications
(42 citation statements)
references
References 102 publications
1
39
0
2
Order By: Relevance
“…Olson et al (2013) suggested that doses of 42 g/day of DHA may be required to reduce disease in humans. Which is in agreement with doses of fish oils used in human trials (1.6-7.1 g/day and averaged 3.5 g/day) that showed improvement in reducing duration of morning stiffness, number of tender or swollen joints, decreasing pain and time to fatigue, increasing grip strength, and decreasing use of non-steroidal anti-inflammatory drugs (reviewed in Calder (2008), and Miles and Calder (2012)). Until the necessary clinical trials are performed utilizing resolvins for inflammatory arthritis it is difficult to predict the dose required for beneficial outcome in humans, although based on their potency we would predict far lower amounts would be required in comparison to the parent compounds DHA or EPA.…”
Section: Resolvins As Therapeutic Tools For Rheumatic Diseasessupporting
confidence: 83%
See 1 more Smart Citation
“…Olson et al (2013) suggested that doses of 42 g/day of DHA may be required to reduce disease in humans. Which is in agreement with doses of fish oils used in human trials (1.6-7.1 g/day and averaged 3.5 g/day) that showed improvement in reducing duration of morning stiffness, number of tender or swollen joints, decreasing pain and time to fatigue, increasing grip strength, and decreasing use of non-steroidal anti-inflammatory drugs (reviewed in Calder (2008), and Miles and Calder (2012)). Until the necessary clinical trials are performed utilizing resolvins for inflammatory arthritis it is difficult to predict the dose required for beneficial outcome in humans, although based on their potency we would predict far lower amounts would be required in comparison to the parent compounds DHA or EPA.…”
Section: Resolvins As Therapeutic Tools For Rheumatic Diseasessupporting
confidence: 83%
“…Such benefits include reduced duration of morning stiffness, reduced number of tender or swollen joints, decreased pain and time to fatigue, increased grip strength, and decreased use of non-steroidal antiinflammatory drugs (reviewed in Calder (2008), and Miles and Calder (2012)). The dose range of omega-3 polyunsaturated fatty acids reported in these trials varied from 1.6 to 7.1 g/day and averaged 3.5 g/day (Calder, 2008;Miles and Calder, 2012). Thus, evidence-based reports implicate fish oil supplementation as an useful complementary therapy for rheumatoid arthritis.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, population studies suggest that these lipids have a preventative effect in rheumatoid arthritis (RA), with lower prevalence observed in the Japanese and Inuit population, who consume large amounts of oily fish rich in omega-3 PUFA. In corroboration, clinical studies have revealed that dietary supplementation with omega-3 PUFA is efficacious in reducing joint pain, morning stiffness, and nonsteroidal anti-inflammatory drugs (NSAID) usage in patients with RA [17]. Additionally, consumption of omega-3 PUFA has favorable effects for cardiovascular health [18], which can become compromised in patients with RA.…”
Section: Proresolving Lipid Agonists: Resolvinsmentioning
confidence: 93%
“…A number of randomized, placebo-controlled, double-blind studies of fish oil treatments have been reported. In different reviews Calder have summarized the results of studies with a dose of fatty acids between 1.6 and 7.1 g/d (average of 3.5 g/day EPA + DHA) and almost of them reported some benefit (Calder, 2006;Calder, 2008b;Galli et al, 2009). Clinical symptoms were improved, including reduced duration of morning stiffness, number of tender or swollen joints, joint pain, time of fatigue and increased grip strength.…”
Section: Efficacy Of Fatty Acids On Human Diseasementioning
confidence: 99%